Evaluation of the edaphic and water properties of Diu coast (Saurashtra, Gujarat, India) in relation to the population density of Avicennia marina - Varsha V. Patale; Jigna G. Tank (Applied Water Science, 2022)
Abstract The Diu Island is the natural habitat dominated by Avicennia marina mangrove species in the southeast coast of Saurashtra in Gujarat State of India. Since it is a famous industrial and tourism place, survival of these mangrove species is threatened due to anthropogenic activities. Therefore, to conserve the natural habitat of Avicennia marina, it is necessary to evaluate the influence of water quality and edaphic factors on growth of Avicennia marina species in this region. In order to study the quality of soil and water, samples were collected from the sediments of five different habitats during each season (summer, winter and monsoon) and physicochemical parameters were measured. The quality of water and soil was influenced by seasonal changes due to change in temperature, pH, macroelements (carbon, oxygen, nitrogen, phosphate, sulfur, potassium, calcium and magnesium) and microelements (zinc, iron, manganese, copper, boron and nickel) content which in turn increases TDS, TSS, TS, alkalinity, COD and BOD of water. These parameters were correlated with the population density of plants growing in the sediments to observe its effect on growth of plants in each habitat. Hence, it was concluded that there was significant influence of seasonal changes on the physicochemical parameters of water and soil which in turn changed the density of plants (site:3 > site:1 > site:2 > site:5 > site:4) at all five sites. Multivariate cluster analysis, MDS and PCA, identified spatial and temporal characteristics of five habitats and suggested that site-4 and site-5 are more polluted as compared to other sites and require restoration and conservation.